PEMAHAMAN KONSEPTUAL DIKAJI DARI GAYA BELAJAR SISWA DALAM MATERI BANGUN DATAR KELAS VIII SMP - Uni Cyntia Clodia; Sugiatno Sugiatno; Dede Suratman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
Abstract This research aims to describe how conceptual understanding is assessed from students' learning styles in class VIII flat building materials at SMPN 20 Pontianak. The research method is descriptive with a survey. The research subjects were nine students of class VIIIA consisting of three students with a visual learning style, three students with an auditory learning style, and three students with a kinesthetic learning style. These results indicate that students who have a visual learning style tend to have moderate conceptual understanding, only research that restates the concepts that have been studied classifies objects based on mathematical concepts and presents concepts in various representations achieved, for students who have auditory learning tend to have an understanding. Low conceptual is only an indicator that is known to be a concept that has been studied, classifies objects based on mathematical concepts, and presents the concept in various fulfilled representations, whereas Students who have a kinesthetic learning style tend to have high conceptual understanding, only indicators of restatement of concepts that have been studied, classifying objects based on mathematical concepts, presenting concepts in various representations and relating internal or externally fulfilled mathematical concepts. Keywords: Conceptual Understanding, Learning style, Two-dimensional Figure